Inexact Infinite Products of Weak Quasi-Contraction Mappings in b-Metric Spaces. (9th September 2020) - Gupta, Anuradha; Rohilla, Manu
Abstract: The influence of errors on the convergence of infinite products of weak quasi-contraction mappings in b -metric spaces is explored. An example demonstrating the necessity of convergence of the sequence of computational errors to zero is also provided. Moreover, we discuss weak ergodic theorems in the setting of b -metric spaces.